Contested Sovereignties: Turkish Diplomacy, the Straits Commission, and the League of Nations (1924–1936). Issue 2 (4th March 2023) - Papuççular, Hazal
ABSTRACT: This article analyzes Turkey's complex relationship with the Straits Commission in the interwar period. The Convention Relating to the Regime of the Straits that was signed in Lausanne in 1923 stipulated the formation of an international commission under the auspices of the League of Nations. This institution became a locus that Turkey, the other members of the Commission and the League of Nations negotiated the sovereignty of the Straits and discussed the authority over its administration. This article shows that Turkey perceived the Commission detrimental to its sovereignty. However, this article also portrays an interesting case study that Turkey conducted diplomacy with this intergovernmental organization in which it actually played a leading role. The vague relationship of the Commission with the League of Nations that Turkey was not a member of until 1932 further complicates the narrative which emphasizes the multiple layers that diplomacy was formed and performed, thereby necessitating new approaches to the study of foreign policy. In this regard, this study aims to transcend the traditional accounts on interwar Turkish diplomacy, which have been dominated by the interstate bilateral relations.